2018
DOI: 10.1186/s40781-018-0176-6
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in free amino acid content and hardness of beef while dry-aging with Mucor flavus

Abstract: BackgroundA mold strain thought to be suitable for dry-aging process was isolated. The information about the scientific aspects of molds related to dry-aging beef is scarce. We, therefore, conducted aging trials to determine the characteristics of the isolated mold strain associated with dry-aging process. Specifically, during the dry-aging of beef with the mold strain, the changes in the free amino acid content, hardness, productive loss, drip and cooking loss were analyzed. These characteristics were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Furthermore, BF muscle produced a significantly lower ratio of tasty and bitter amino acids than the unaged as well as the 10 and 15-day wet-aged meat. On the other hand, some free amino acids decreased or remained constant during the aging process due to an increase in mold strain [34]. Therefore, wet-aging enhances the tasty amino acids for both muscles.…”
Section: Free Amino Acidsmentioning
confidence: 99%
“…Furthermore, BF muscle produced a significantly lower ratio of tasty and bitter amino acids than the unaged as well as the 10 and 15-day wet-aged meat. On the other hand, some free amino acids decreased or remained constant during the aging process due to an increase in mold strain [34]. Therefore, wet-aging enhances the tasty amino acids for both muscles.…”
Section: Free Amino Acidsmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors reported that the modifications they requested to the data in Tables 1 , 2 and 3 were incorrectly implemented due to a misunderstanding in mark-ups. Also, the titles of the tables should be modified as follows:…”
Section: Correctionmentioning
confidence: 99%
“…Despite numerous studies on Mucoromycotina in a pathogenic context their basic biology remains understudied. We selected two Umbelopsis isolates from soil: U. isabellina and U. vinacea , two soil-derived Mucor isolates: M. circinatus and M. plumbeus , and two Mucorales representatives: Thamnidium elegans and M. saturninus with proteolytic capabilities enabling them to colonize dung and animal substrate ( Hanagasaki and Asato, 2018 ). Two strains were obtained from the CBS-KNAW culture collection and the remaining four were selected from the Mucoromycotina collection of University of Warsaw Herbarium.…”
Section: Introductionmentioning
confidence: 99%